Ranching For The Birds - Jane B. Koger (Symphony in the Flint Hills, 2010)
After 30 years raising cattle in southeastern Chase County, I’ve started telling people that ranching is for the birds. Let me give you some context.
Keywords: prairie chicken; birds; ranching; cattle; cows; grassland; prairie; Chase County; Roy Beedle; game; rural; bobwhite quail; spring; farm; tradition; native; animals